Environment of paleomire of lignite seams of Bikaner-Nagaur basin, Rajasthan (W. India): petrological implications. (3rd October 2019) - Rajak, Pramod K.; Singh, Vijay K.; Singh, Prakash K.; Singh, Mahendra P.; Singh, Alok K.
Petrological and chemical investigations of lignites from the Bikaner-Nagaur Basin, Rajasthan (Western India) have been undertaken to understand their petrographic characteristics and the paleomire. The huminite reflectance (VRr) (0.21-0.26%) put these lignites as 'low rank C' coals. Huminite is the most abundant maceral group which is dominated by detrohuminite (densinite and attrinite). Telohuminite (chiefly ulminite-A and ulminite-B) occurs next in abundance. Liptinite and inertinite occur in subordinated amount. High GI and low TPI values indicate a continuous wet condition in the basin with a slow rate of subsidence. However, Gurha lignites, suffered few spell of relatively drier period as revealed by increased inertinite content in few bands. The study indicates a limno-telmatic swamp and a slow fall in ground water table. Petrography based models suggest a wet moor condition having a moderate flooding with increasing bacterial activity that prevailed under coastal-marshy setting during the transgressive phase. [Received: February 18, 2017; Accepted: September 21, 2017]